Leveraging SWOT Analysis for Effective Electric Vehicle Marketing: A Literature Review - Adekoya, Dare Oluwatobi (Journal of Business, Innovation and Sustainability (JBIS), 2024)
With the rise of electric vehicles (EVs) as a sustainable alternative to traditional vehicles, understanding the market dynamics is essential for stakeholders. This study investigates the impact of SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis on the marketing strategies of EVs. The research synthesizes existing knowledge, examining EV advantages such as zero emissions and lower operating costs, alongside disadvantages like limited range and high initial costs. It also addresses challenges from internal combustion engines, supply chain issues, and regulatory uncertainties, while exploring opportunities in government subsidies and technological advancements. The methodology involves a comprehensive literature review to provide a holistic view of the EV market. Key findings indicate that despite significant benefits, several challenges hinder widespread EV adoption. This study highlights areas for improvement and strategic focus for industry stakeholders and policymakers. Future efforts should enhance battery technology, expand charging infrastructure, and establish robust regulations to promote EV proliferation and support sustainable transportation.